2001
DOI: 10.1021/bp010046b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Water-Soluble Polysaccharides on Bacterial Cellulose Production in a 50-L Airlift Reactor

Abstract: Bacterial cellulose (BC) production was carried out in a batch cultivation of Acetobacter xylinum in a 50-L internal loop airlift reactor by addition of water-soluble polysaccharides into the medium. When 0.1% (w/w) agar was added, BC production reached 8.7 g/L compared with 6.3 g/L in the control, and duration of the cultivation period to reach the maximum concentration of BC was almost half of that without addition of polysaccharides. During cultivation, BC was formed into pellets whose size was smaller when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 19 publications
(26 reference statements)
1
23
0
1
Order By: Relevance
“…Although other polymeric additives such as xanthan, agar, acetan were investigated to hinder formation of large clumps of BC and enhance BC production in either jar fermentor or airlift reactor, there are remarkable diVerences in BC enhancing extent according to diVerent strains, additives and additives concentration [1,3,9]. Bae et al [1] reported that the maximum BC production of A.xylinum BPR2001 at 0.4% (w/v) agar was 12.8 g/l compared with xylinum NUST4.1 in the medium containing NaAlg in the shake Xask.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other polymeric additives such as xanthan, agar, acetan were investigated to hinder formation of large clumps of BC and enhance BC production in either jar fermentor or airlift reactor, there are remarkable diVerences in BC enhancing extent according to diVerent strains, additives and additives concentration [1,3,9]. Bae et al [1] reported that the maximum BC production of A.xylinum BPR2001 at 0.4% (w/v) agar was 12.8 g/l compared with xylinum NUST4.1 in the medium containing NaAlg in the shake Xask.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there are a few reports stating that addition of water-soluble polymers such as xanthan, agar, polyacrylamide-co-acylic acid (PCA), and acetan can increase relative viscosity of the broth to reduce shear stress, hinder coagulation of BC during the cultivation to form uniform smaller pellets, which are advantageous to transfer nutrients and oxygen into bacterial cells located inside and on the surface of the cellulose matrix, and further promote BC productivity into the medium, will assist in enhancing BC productivity [1,3,9,10]. On the other hand, various watersoluble polymers added into the medium are known to interfere with the aggregation of microWbrils into a normal ribbon assembly, aVect the crystallization of cellulose I and I and introduce the characteristic properties of these additives to attain BC composite materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…The production of biodegradable thermoplastics from bacterial polyhydroxyalkanoates synthesized by Ralstonia eutropha in a membrane ALR (446) and a DT-ALR (447) has been examined. Obtaining of bacterial cellulose from cultures of Acetobacter xylinum in a DT-ALR has also been documented (448,449).…”
Section: Biopolymersmentioning
confidence: 99%
“…The concentration of BC was doubled and the production rate was 0.116 g L −1 h −1 , which is twice that of an air supplied culture and comparable with that in a mechanically agitated stirred-tank fermentor. Chao et al 40 using the 50 L internal-loop airlift reactor discovered that when 0.1% (w/w) agar (water-soluble polysaccharide) was added, BC production reached 8.7 g L −1 compared with 6.3 g L −1 in the control medium using Acetobacter xylinum subsp. sucrofermentans (BPR2001).…”
Section: Effect Of the Type Of Reactor On Productionmentioning
confidence: 99%